2019
DOI: 10.1002/adma.201806443
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Orbital‐Oriented Control of Magnetization in Half‐Metallic La0.7Sr0.3MnO3 Films

Abstract: Manipulating spins by ultrafast pulse laser provides a new avenue to switch the magnetization for spintronic applications. While the spin–orbit coupling is known to play a pivotal role in the ultrafast laser‐induced demagnetization, the effect of the anisotropic spin–orbit coupling on the transient magnetization remains an open issue. This study uncovers the role of anisotropic spin–orbit coupling in the spin dynamics in a half‐metallic La0.7Sr0.3MnO3 film by ultrafast pump–probe technique. The magnetic order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ mechanisms involved with Elliot-Yafet scattering 10,[41][42][43] and spin current 6,7,11,44 have been discussed. Very recently, a quantitative study and comparison between fluence-dependent experiments and a model that includes non-equilibrium effects microscopically has been reported 45 .…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ mechanisms involved with Elliot-Yafet scattering 10,[41][42][43] and spin current 6,7,11,44 have been discussed. Very recently, a quantitative study and comparison between fluence-dependent experiments and a model that includes non-equilibrium effects microscopically has been reported 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Behind the phenomena, the mechanism of magneto-optic coupling is the interaction between spin and photon. [14] It contains two possible channels: one is direct spin-photon interaction; the other one is indirect spin-photon interaction.…”
Section: Two Mechanisms Of Interaction Between Spin and Photonmentioning
confidence: 99%
“…[7] Needless to say, understanding the EPC is also important for such nonsuperconducting oxides to reveal their underlying microscopic mechanisms. [8,9] Transition-metal perovskite LaCoO 3 exhibits a diamagnetic insulating low-spin phase (t 6 2g e 0 g , S = 0) at low temperatures, whereas it becomes metallic at higher temperature with the Co ions assuming a higher spin state (t 4 2g e 2 g , S = 2 or t 5 2g e 1 g , S = 1). [10][11][12][13][14] Recently, it was found that epitaxial tensile-strained LaCoO 3 thin films become ferromagnetic below 85 K, [15][16][17][18] exhibiting application potentials in magnetic devices.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Needless to say, understanding the EPC is also important for such non‐superconducting oxides to reveal their underlying microscopic mechanisms. [ 8 , 9 ]…”
Section: Introductionmentioning
confidence: 99%